Pengaruh Labelisasi Halal Dan Harga Terhadap Keputusan Pembelian Produk Mie Samyang (Studi Kasus Pada Mahasiswa FEB Unisma Angkatan 2018) - Rumkel, Abdul Rahman; Djaelani, Abdul Kodir; Hardaningtyas, Ratna Tri (E-JRM : Elektronik Jurnal Riset Manajemen, 2025)
Abstract This study aims to determine the effect of halal labeling and price on purchasing decisions for samyang noodle products (Case Study of Students of the Faculty of Economics and Business, Islamic University of Malang, Class of 2018). The type ofresearch used is explanatory research with a quantitative approach. The sample inthis study obtained 55 respondents with the technique used in this study purposive sampling. The results showed that halal labeling and price simultaneously had a positive and significant effect on purchasing decisions. Recently, many products that have not been halal certified have resulted in consumers, especially Muslim consumers, finding it difficult to distinguish which products are truly halal and can be consumed in accordance with Islamic law from products that are not haram. It is presumed that most of the snack products on the market are not clearly halal. Therefore, the halalness of a product is a mandatory requirement for Muslims, be it food, medicine or other consumer goods. Keywords: Halal Labeling, Price, and Purchase Decision.